Peplau's Theory of Interpersonal Relations: An Alternate Factor Structure for Patient Experience Data?. (April 2017) - Hagerty, Thomas A.; Samuels, William; Norcini-Pala, Andrea; Gigliotti, Eileen
A confirmatory factor analysis of data from the responses of 12, 436 patients to 16 items on the Consumer Assessment of Healthcare Providers and Systems–Hospital survey was used to test a latent factor structure based on Peplau's middle-range theory of interpersonal relations. A two-factor model based on Peplau's theory fit these data well, whereas a three-factor model also based on Peplau's theory fit them excellently and provided a suitable alternate factor structure for the data. Though neither the two- nor three-factor model fit as well as the original factor structure, these results support using Peplau's theory to demonstrate nursing's extensive contribution to the experiences of hospitalized patients.